2005
DOI: 10.1007/s00204-004-0642-4
|View full text |Cite
|
Sign up to set email alerts
|

New metabolites of di(2-ethylhexyl)phthalate (DEHP) in human urine and serum after single oral doses of deuterium-labelled DEHP

Abstract: The metabolism of di(2-ethylhexyl)phthalate (DEHP) in humans was studied after three doses of 0.35 mg (4.7 microg/kg), 2.15 mg (28.7 microg/kg) and 48.5 mg (650 microg/kg) of D4-ring-labelled DEHP were administered orally to a male volunteer. Two new metabolites, mono(2-ethyl-5-carboxypentyl)phthalate (5cx-MEPP) and mono[2-(carboxymethyl)hexyl]phthalate (2cx-MMHP) were monitored for 44 h in urine and for 8 h in serum for the high-dose case, in addition to the three metabolites previously analysed: mono(2-ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
401
2
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 494 publications
(427 citation statements)
references
References 29 publications
15
401
2
9
Order By: Relevance
“…Our workers were most likely exposed to phthalates by inhalation or dermal contact. Koch et al (2005a) found no dose dependency in DEHP metabolism and excretion (dose range: 4.7 to 650 mg/kg). Although one of our workers had a DEHP daily intake estimate 4800 mg/kg/day, 95% of our workers had DEHP estimates that were o70 mg/kg/day.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our workers were most likely exposed to phthalates by inhalation or dermal contact. Koch et al (2005a) found no dose dependency in DEHP metabolism and excretion (dose range: 4.7 to 650 mg/kg). Although one of our workers had a DEHP daily intake estimate 4800 mg/kg/day, 95% of our workers had DEHP estimates that were o70 mg/kg/day.…”
Section: Discussionmentioning
confidence: 78%
“…Nonetheless, with 9-25 workers per sector, some of this temporal variability was likely averaged across workers. Temporal variability in metabolite concentrations is further heightened by the metabolites' relatively short half-lives and rapid elimination in the urine (Anderson et al, 2001;Api, 2001;Koch et al, 2005aKoch et al, , 2004. Within-person variability in urinary phthalate metabolite concentrations has been shown to depend on the population, phthalate metabolite, and time frame of interest (Hoppin et al, 2002;Hauser et al, 2004;Fromme et al, 2007;Teitelbaum et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination half-life of MEHP has been reported as 5 h in a human metabolism experiment (Koch et al, 2005b), so that 24 h after exposure, five halflives have passed, and only about 3% of the total mass of MEHP that was formed by the exposure remains to be eliminated. It is easy to see that a day following an exposure to DEHP, the concentration of MEHP could be very low or fall below a detection limit.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, secondary metabolites could be still forming if their rate of formation and excretion is slower than that of MEHP. Koch et al (2005b) measured four additional metabolites of DEHP in the experiment, and found that these secondary metabolites of DEHP have elimination half-lives in the range of 10-15 h. This implies that MEHP might be a poor candidate as an indication of exposure to DEHP. Indeed, Barr et al (2003) advocated the urinary analysis of secondary metabolites of phthalates as perhaps better indicators of exposure, compared with the monoester primary phthalate metabolites, for just this reason.…”
Section: Introductionmentioning
confidence: 99%